Diet quality is associated with disability and symptom severity in multiple sclerosis. (2nd January 2018) - Fitzgerald, Kathryn C.; Tyry, Tuula; Salter, Amber; Cofield, Stacey S.; Cutter, Gary; Fox, Robert; Marrie, Ruth Ann
Abstract : Objective: To assess the association between diet quality and intake of specific foods with disability and symptom severity in people with multiple sclerosis (MS). Methods: In 2015, participants in the North American Research Committee on MS (NARCOMS) Registry completed a dietary screener questionnaire that estimates intake of fruits, vegetables and legumes, whole grains, added sugars, and red/processed meats. We constructed an overall diet quality score for each individual based on these food groups; higher scores denoted a healthier diet. We assessed the association between diet quality and disability status as measured using Patient-Determined Disease Steps (PDDS) and symptom severity using proportional odds models, adjusting for age, sex, income, body mass index, smoking status, and disease duration. We assessed whether a composite healthy lifestyle measure, a healthier diet, healthy weight (body mass index <25), routine physical activity, and abstinence from smoking was associated with symptom severity. Results: Of the 7, 639 (68%) responders, 6, 989 reported physician-diagnosed MS and provided dietary information. Participants with diet quality scores in the highest quintile had lower levels of disability (PDDS; proportional odds ratio [OR] for Q5 vs Q1 0.80; 95% confidence interval [CI] 0.69–0.93) and lower depression scores (proportional OR for Q5 vs Q1 0.82; 95% CI 0.70–0.97). Individuals reporting a composite healthy lifestyle had lower odds of reporting severe fatigue (0.69; 95% CI 0.59–0.81), depression (0.53; 95% CI 0.43–0.66), pain (0.56; 95% CI 0.48–0.67), or cognitive impairment (0.67; 95% CI 0.55–0.79). Conclusions: Our large cross-sectional survey suggests a healthy diet and a composite healthy lifestyle are associated with lesser disability and symptom burden in MS.